Altered Visuospatial Processing in Schizophrenia: An Event-related Potential Microstate Analysis Comparing Patients with and without Hallucinations with Healthy Controls. (15th December 2021) - Antonova, Ingrida; van Swam, Claudia; Hubl, Daniela; Griskova-Bulanova, Inga; Dierks, Thomas; Koenig, Thomas
Highlights: Amplitude of the occipital visual N1 is reduced in schizophrenia patients. N1 reduction is most prominent over the right hemisphere in hallucinating patients. P3b is partially replaced by P3a in schizophrenia patients without hallucinations. Specific changes in ERPs can be associated with the prevalence of hallucinations. Abstract: Patients with schizophrenia present with various symptoms related to different domains. Abnormalities of auditory and visual perception are parts of a more general problem. Nevertheless, the relationship between the lifetime history of auditory verbal hallucination (AVH), one of the most prevalent symptoms in schizophrenia, and visuospatial deficits remains unclear. This study aimed to investigate differences in hemispheric involvement and visuospatial processing between healthy controls (HCs) and schizophrenia patients with and without AVHs. HCs ( N = 20), schizophrenia patients with AVH (AVH group, N = 16), and schizophrenia patients without hallucinations (NH group, N = 10) participated in a 4-choice reaction task with lateralized stimuli. An event-related potential (ERP)-microstate approach was used to analyze ERP differences between the conditions and groups. The schizophrenia patients without hallucinations had slower responses than the HCs. An early visual N1 contralateral to stimulation side was prominent in all groups of participants but with decreased amplitude in the patients with schizophrenia, especially in the AVH group over the right hemisphere. The amplitude of P3b, a cognitive evaluation component, was also decreased in schizophrenia. Compared to AVH and HC groups, the patients in the NH group had altered microstate patterns: P3b was replaced by a novelty component, P3a. Although the difference between both patient groups was only based on the presence of AVHs, our findings indicated that patients had specific visuospatial deficits associated with a lifetime history of hallucinations: patients with AVHs showed early visual component alterations in the right hemisphere, and those without AVHs had more prominent visuospatial impairment.